SELF DIRECTED LEARNING: MENINGKATKAN KEPERCAYAAN DIRI DALAM BERBICARA BAHASA ARAB - Fajariyah, Hamzatul; Umar Manshur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Arabic in Indonesia is taught because of its relationship with Islamic teachings, but the ability to speak this language is often not optimal. Self Directed Learning which gives students the freedom to manage their learning process is considered a potential method to improve speaking skills. This study aims to explore the Self Directed Learning method in increasing students' confidence in speaking Arabic at the Foreign Language Development Institute of PP. Nurul Jadid Paiton Probolinggo. This research uses a qualitative approach with case studies, collecting data through observation, interviews, and documentation. The findings of the study show that the two most significant processes of Self Directed Learning in increasing confidence in speaking are presentation of learning outcomes and monitoring of learning outcomes. This study suggests that Self Directed Learning can be an effective method in building students' confidence, especially in actively speaking Arabic.